Relationship between gross motor function of cerebral palsy children and quality of life of their primary caregivers - Kumari, Somal; Ali, Syed Shahzad; Ahmed Mirza Baig, Aftab (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the relationship between gross motor function of children with cerebral palsy and quality of life of their primary caregivers. Method: The cross-sectional analytical study was conducted from December 2020 to August 2021 at the Sindh Institute of Physical Medicine and Rehabilitation and the Rabia Moon Trust, Karachi, and comprised children with cerebral palsy and their caregivers. The children were assessed on the basis of Gross Motor Function Measure-66 and Gross Motor Functional Classification System, while the caregivers were asked to complete the self-administered World Health Organisation Quality of Life-BREF questionnaire. All the categorical variables were presented through frequencies and percentages. Spearman’s Correlation was applied to evaluate the correlation. Data was analysed using SPSS 16. Results: Of the 43 children, 26(60.5%) were male and 17(39.5%) were females. The overall mean age was 5.70±1.820 years. Among the caregivers, 40(93%) were females and 3(7%) were males. The mean age of the caregivers was 27.70±4.77 years. None of domains of quality of life showed significant correlation with total score of Gross Motor Function Measure-66 (p>0.05). Conclusion: The disease severity among children with cerebral palsy was not a factor associated with quality of life of the caregivers. The physical health was relatively lower among the caregivers, but it was not associated with motor disabilities. Key Words: Caregiver burden, Child development disorders, Correlation, Developmental, Disabilities, Family caregivers.